Investigating the Relationship between Business Process Orientation and Social Capital. (5th February 2014) - Zarei, Behrouz; Chaghouee, Yahya; Ghapanchi, Amir Hossein
<x xml:space="preserve">Abstract</x> The purpose of this paper is to identify the relationship between business process management and organizational intangible assets, in general, and their social capital, in particular. To uncover this association, a research model is developed and statistically tested. Data was collected from 103 managers of process‐based companies and was subsequently analyzed using Structural Equation Modeling (SEM). Our analysis demonstrates that better management of business processes in organizations can lead to the enhancement of social capital through the reinforcement of cooperation, customer orientation and organizational communication. The results can be used by various organizations to find out the importance of their process management practices for enhancing their social capital. Copyright © 2014 John Wiley & Sons, Ltd.